A trans-cultural study of the practice of occupational therapists in Thailand and Australia: reframing theories of practice - Pongsaksri, Arisa (Curtin University, 2004)
Culturally appropriate conceptual models for practice are of major interest to occupational therapists, an emerging health profession in Thailand. Currently in Thailand, occupational therapy education and practice derives its conceptual models from Western models. How these models are translated into practice in Thailand is unclear, as there are currently no research studies relating to the cultural and clinical practice demands of Thai occupational therapists and of service delivery in Thailand. In addition, how occupational therapists in Australia apply conceptual models in practice has also been given limited attention in the research literature. A comparison is made between Thai and Western Australian occupational therapists to examine the use of theoretical models in the Western cultural context and to investigate the influences of cultural differences on occupational therapy practice. The purpose of this study is to identify the conceptual models most frequently used by occupational therapists in Thailand and in Australia, to describe the application of these models to practice, and to explore the cultural influences impacting on the application to practice. The need for a derived but more culturally specific conceptual model for occupational therapy practice in Thailand was also investigated. Focus group interviews were conducted as the initial stage of the study, to obtain in-depth background information about occupational therapy practice. Content analysis using transcript-based analysis and systematic coding was used to analyse the focus group data. The results demonstrated three main conceptual approaches: among both Westem Australian and Thai occupational therapists. These three models were described as the Performance Model, the Whole Person Model, and the Medical Model.The findings from focus group interviews and related literature were used to develop a questionnaire. The questionnaire was designed as a self-report measure, using a 4 point scale ranging from ‘strongly agree’ to ‘strongly disagree’. It was arranged in 4 parts: Part A-Background Information, Part B- Models of Occupational Therapy Practice, Part C-Occupational Therapy Practice, and Part D-Practice Comment. Parts A, B and C consisted of closed-ended questions, whereas Part D was constructed to elicit open-ended questions. The survey data was collected from 138 Thai occupational therapists (ThaiOTs) and 155 Western Australian occupational therapists (WAOTs). A Chi-square test result demonstrated that ThaiOTs favoured the Medical Model for practice whilst WAOTs used the Performance Model and the Whole Person Model (p < 0.05). Principal component factor analysis was used to identify significant factors differentiating the practice of WA and Thai occupational therapists and to guide the development of the model of practice for ThaiOTs. The Mann-Whitney U Test results showed clear differences of therapist practice between Australia and Thailand in relation to their views about Clients, Professional Perspective (Therapists), Intervention, Cultural Implications, and Health Care Systems due to the influence of the culture and socio-cultural environment (p < 0.05). The outcomes from all stages in the study were used to develop a model of practice for Thai occupational therapists. This model named the ‘Samphan’ Framework of Practice focuses on the client and family as an inseparable unit, which differs from an individual, or client focus central to most Western models.